Pengaruh Debt to Equity Ratio (DER), Firm Size, dan Sales Growth Terhadap Corporate Social Responsibility (CSR) dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2017-2021 - Mellysa Ramadhani; Listrioni Listrioni; Rizki Filhayati Rambe; Desi Ika (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research aims to determine the effect of Debt to Equity Ratio, Firm Size, and Sales Growth on Corporate Social Responsibility with Profitability as a Moderating variable in Manufacturing Companies on the Indonesia Stock Exchange (BEI) for the 2017-2021 period. The population in this research is manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. This research is a type of associative research. The number of samples in this research was 77 companies from 216 populations during 5 consecutive years of observation so that the total sample was 850 data observations. The analysis technique used is Moderated Regression Analysis (MRA). Data collection techniques use literature study and documentation through the official website of the Indonesian Stock Exchange, namely www.idx.co.id. The research results show that the Debt to Equity Ratio, Firm Size, and Sales Growth variables have a positive and significant effect on Corporate Social Responsibility disclosure in manufacturing companies in 2017-2022. Profitability cannot moderate the influence of Debt to Equity Ratio, Firm Size, and Sales Growth on Corporate Social Responsibility disclosure in Manufacturing companies listed on the IDX in 2017-2021.